Physical development of children from Bydgoszcz voivodeship - Nowicki, Grzegorz (Anthropological Review, 1975)
Measurements of stature and body weight of children and adolescents (age range 7.5–18.5 years) were carried in Bydgoszcz voivodeship between 15th and 30th May 1971. The author has examined 41443 individuals (including 20948 females) from various schools (primary and high schools, professional courses etc.). Results of these investigations are compared with observations made in 1937, 1946, 1951 and 1971 in the same region and also with mean stature and weight for children from whole Poland computed in 1966. Children examined in this study have higher mean values of stature and weight than individuals of the same ages investigated in 1937. This reflects an improvement in life conditions during last 34 years.